The Influence Of Service Quality, Price Perceptions And Facilities On Customer Satisfaction At The Siliwangi Futsal Centre Tasikmalaya City - Sabiq Abdul Basit; Arga Sutrisna; Suci Putri Lestari (Journal of Indonesian Management, 2023)
The purpose of this study was to determine the effect of service quality, perception of price and pacilities simultaneously or partially on consumer statisfaction of Siliwangi Futsal Center in Tasikmalaya City. Survey of Siliwangi Futsal Center consumers in Tasikmalaya City. The research method used is descriptive and verification method. The sample in this study amounted to 100 respondents. Data collection was carried out using a questionnaire. The data analysis used is multiple regression analysis. The results of this study indicate that service quality, perception of price and pacilities simultaneously have a significant effect on consumer satisfaction. Partially, service quality has a significant effect on consumer satisfaction. Partially price perception has no significant effect on consumer satisfaction. Partially, the pacilities has a significant effect on consumer satisfaction.